VO#029 Proposal for drainage box works - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of the proposal of cost amount against the execution and completion of drainage box works for BRACU new campus project.